The Role of Self-efficacy Towards Student Involvement in Grade VII Female Students of SMP (Junior High School) at Islamic Boarding School of Darul Hijar Puteri Martapura - Mariamita, Dewi; Akbar, Sukma Noor; Rachmah, Dwi Nur (Universitas Lambung Mangkurat, 2021)
The purpose of this study was find out the role of self-efficacy towards student involvement in the seventh grade female students of SMP (Junior High School) at Islamic Boarding School of Darul Hijrah Puteri, Martapura. The population in this study was the students of SMP at Islamic Boarding School of Darul Hijrah Puteri, Martapura. The subjects were 80 seventh grade students of SMP at Islamic Boarding School of Darul Hijrah Puteri, Martapura, who were selected using a simple random sampling technique. Data were collected using two psychological scales including a scale of self-efficacy and a scale of student involvement. Data were analyzed using a simple linear regression technique. Based on the results of simple linear regression analysis, it was found that t count > t table (6.135 > 1.990), indicating that there was a positive role of self-efficacy towards student involvement in the seventh grade students of SMP at Islamic Boarding School of Darul Hijrah Puteri, Martapura. A positive value on value t indicated that the higher the self-efficacy, the higher the student involvement; conversely, the lower the self-efficacy, the lower the student involvement. The results of this analysis prove that the hypothesis stating that there is a role of self-efficacy towards student involvement can be accepted. The coefficient of determination shows the role of self-efficacy towards student involvement is 31.7%, while 63.3% is influenced by other factors not included in this study. Keywords: Self-efficacy, student involvement, islamic boarding school